Respuesta :
Equation: 3(a-4)+1=9-a
First, distribute.
3a-12+1=9-a
Combine like terms (12+1).
3a-13=9-a
Add a to both sides.
4a-13=9
Add 13 to both sides.
4a=22
Divide both sides by 4.
a=5.5
Your answer would be a=5.
I hope this helps :)
Answer,
a = 5
Explanation,
Step 1: Simplify both sides of the equation
3(a−4) + 1 = 9 − a
(3)(a) + (3)(-4) + 1 = 9 + -a (Distribute)
3a + − 12 + 1 = 9 + − a
(3a) + (−12 + 1) = − a + 9 (Combine Like Terms)
3a + −11 = −a + 9
3a − 11 = − a + 9
Step 2: Add a to both sides
3a − 11 + a = −a + 9 + a
4a − 11 = 9
Step 3: Add 11 to both sides
4a − 11 + 11 = 9 + 11
4a = 20
Step 4: Divide both sides by 4
4a/4 = 20/4
a = 5
Hope this helps :-)